Givetian (Middle Devonian) historical bio‐ and chronostratigraphical subdivision based on conodonts. (5th October 2016) - Liao, Jau‐Chyn; Valenzuela‐Ríos, José I.
Abstract : The conodont record supports the intended threefold subdivision of the Givetian as envisaged by the International Subcommision on Devonian Stratigraphy into Lower, Middle and Upper Givetian substages. The lower boundary of the Lower Givetian Stage coincides with the lower boundary of the Givetian and it is recognized with the entry of Polygnathus hemiansatus . The lower boundary of the Middle Givetian is identified with the entry of either P .  varcus or P. rhenanus . The base of the Upper Givetian is defined with the entry of Schmidtognathus hermanni . The historical review shows the conceptual evolution from a stage with just one and a half zones to one with ten zones that are the basis for the threefold Givetian subdivision. This zonation is mostly based on evolutionarily related conodont genera that are common in pelagic environments. An alternative conodont zonation for shallow‐water facies for the Lower and Middle Givetian can also be widely applied. The proposal of subdividing the disparilis Zone into three subzones is not accepted.